Trade union cooperation in Europe : patterns, conditions, issues (2020)
We are grateful for the funding of two research projects, on which this book is based. The first was called Can Trade Unions Within Europe Cooperate? It was sponsored by the Swedish Council for Working Life and Social Research (FAS 2008–0246), for the period 2009–2011, with Bengt Furåker as principal investigator. The second project, which was a continuation of the first one, had the title Conditions for and Obstacles to Trade Union Cooperation in Europe. A Comparative Study of Countries and Sectors. It was headed by Bengt Larsson and funded by Riksbankens Jubileumsfond (RJ P13– 0776:1), 2014–2016. We are also grateful for the additional grant that Riksbankens Jubileumsfond gave to finance Open Access publication of the book (RJ P13–0776:6 OA). During the course of our studies we have had several collaborators.